2016
DOI: 10.1096/fj.201600618r
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase‐like phosphodiesterase 3b mediates radiation‐induced damage of renal podocytes

Abstract: The molecular mechanisms responsible for the development of proteinuria and glomerulosclerosis in radiation nephropathy remain largely unknown. Podocytes are increasingly recognized as key players in the pathogenesis of proteinuria in primary and secondary glomerular disorders. The lipid-modulating enzyme sphingomyelin phosphodiesterase acid-like 3B (SMPDL3b) is a key determinant of podocyte injury and a known off target of the anti-CD20 antibody rituximab (RTX). The current study investigates the role of sphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 35 publications
(50 reference statements)
9
78
0
Order By: Relevance
“…In the pathogenesis of Wilson disease and heart disease, aSMase and ceramide accumulation have been shown to be involved in apoptosis of various causes (87)(88)(89)(90). Two studies indicated that ceramide, as a downstream product of activated aSMase, is crucially involved in the apoptosis of pulmonary epithelial cells and renal podocytes, indicating that ceramide perhaps not only mediates acute cellular stress but also participates in progressive tissue degeneration (91,92). In particular, the direct regulatory effect of aSMase and ceramide on mitochondrial dysfunction was related to suppression of the mitochondrial respiratory chain (92).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pathogenesis of Wilson disease and heart disease, aSMase and ceramide accumulation have been shown to be involved in apoptosis of various causes (87)(88)(89)(90). Two studies indicated that ceramide, as a downstream product of activated aSMase, is crucially involved in the apoptosis of pulmonary epithelial cells and renal podocytes, indicating that ceramide perhaps not only mediates acute cellular stress but also participates in progressive tissue degeneration (91,92). In particular, the direct regulatory effect of aSMase and ceramide on mitochondrial dysfunction was related to suppression of the mitochondrial respiratory chain (92).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies indicated that ceramide, as a downstream product of activated aSMase, is crucially involved in the apoptosis of pulmonary epithelial cells and renal podocytes, indicating that ceramide perhaps not only mediates acute cellular stress but also participates in progressive tissue degeneration (91,92). In particular, the direct regulatory effect of aSMase and ceramide on mitochondrial dysfunction was related to suppression of the mitochondrial respiratory chain (92). In renal tubular epithelial cells, it has been suggested that the addition of troxerutin increases the SM content through galactose-3-O-sulfotransferase-1 and sphingomyelin phosphodiesterase-1, which are involved in SM metabolism (94), and inhibits the expression of SMase, thereby reducing ceramide and lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, SMPDL-3b was recently identified as a key molecule in proteinuric glomerular diseases such as focal segmental glomerulosclerosis (FSGS), 1,3,4 diabetic nephropathy 5 and radiation-induced glomerulopathy. 6 Importantly, decreased expression of SMPDL-3b has been reported in podocytes from patients with post-transplant recurrent FSGS, due to alterations in the podocyte cytoskeleton after exposure to sera from patients with FSGS. 1 Furthermore, pretreatment with rituximab (RTX), a specific antibody to human CD20, had a protective effect against such unfavorable alterations in podocytes.…”
mentioning
confidence: 99%
“…SMPDL‐3b has been reported to be involved in macrophage‐related innate immunity, as well as in regulation of the podocyte cytoskeleton . Furthermore, SMPDL‐3b was recently identified as a key molecule in proteinuric glomerular diseases such as focal segmental glomerulosclerosis (FSGS), diabetic nephropathy and radiation‐induced glomerulopathy . Importantly, decreased expression of SMPDL‐3b has been reported in podocytes from patients with post‐transplant recurrent FSGS, due to alterations in the podocyte cytoskeleton after exposure to sera from patients with FSGS .…”
mentioning
confidence: 99%
See 1 more Smart Citation